Molecular characterization and biological activity of bovine interferon-omega3. (December 2017) - An, Dong; Guo, Yongli; Bao, Jun; Luo, Xiuxin; Liu, Ying; Ma, Bo; Gao, Mingchun; Wang, Junwei
Abstract: Bovine interferon-omega3 (BoIFN-ω3) gene was amplified from bovine liver genomic DNA, which encodes a 195-amino acid protein containing a 23-amino acid signal peptide. Analysis of the molecular characteristics revealed that BoIFN-ω3 evolving from IFN-ω, contained four cysteine residues and five alpha helices, showing that BoIFN-ω3 presented the typical molecular characteristics of type I interferon. BoIFN-ω3 exhibited antiviral and antiproliferative activities, which exerted a protective effect against VSV in several mammalian cell lines, as well as against BEV, IBRV, and BVDV in MDBK cell. Moreover, BoIFN-ω3 was shown to be highly sensitive to trypsin, but remaining stable despite changes in pH and temperature. Additionally, BoIFN-ω3 induced the transcription of Mx1, ISG15, and ISG56 genes, as well as the expression of Mx1 protein in a time-dependent manner. These findings will be useful to further study BoIFN-ω in host's defence against infectious diseases, particularly viral infections. Furthermore, results will facilitate further research on the bovine interferon family. Highlights: BoIFN-ω3 presents antiviral activity on several mammalian cell lines and protective effect against VSV, BEV, IBRV, and BVDV. BoIFN-ω3 exhibits antiproliferative activity and insensitivity to pH and temperature. BoIFN-ω3 can activate the transcription of ISGs gene, as well as the expression of Mx1 in a time-dependent manner.